Relationship of Fungal Vaginitis Therapy to Prior Antibiotic Exposure. Issue 3 (2003) - Glover, Douglas D.; Larsen, Bryan
Abstract : Objective: To address the putative association of antibiotic use and subsequent yeast vaginitis in a population of non-pregnant women. Methods: Three hundred and sixteen women who received medical care in rural family medicine clinics enrolled in this study. Participants were pre-menopausal and non-pregnant and were followed until they used a course of antifungal therapy for vaginitis, became pregnant or moved from the catchment area. At entry subjects were free of vaginitis symptoms and had taken no antibiotics for 30 days. Patients were followed by repeated review of clinic records, hospital records and telephone or personal interviews. Data collection included documentation of episodes of antifungal treatment for vulvovaginal candidiasis and confirmed antibiotic treatment or credible history of antibiotic use prior to the use of antifungal therapy. Physician-reported uses of antibiotic and antifungal as well as patient-reported uses of these were recorded. Results: There were four reported cases of antifungal therapy following within a month of antibiotic use, in contrast to 484 antibiotic uses not followed by antifungal use. If time of observation was extended to 6 months from antibiotic use, there were 13 uses of antifungal therapy after antibiotics and 475 uses of antibiotics not followed by antifungal therapy. Conclusion: Our results cast doubt on the association of antibiotics as a putative cause of yeast vulvovaginitis.